Functional encryption - Ahmad, Khairol Amali Bin; Ahmad, Khaleel; Dulhare, Uma N. (EAI/Springer Innovations in Communication and Computing, 2021)
This book provides awareness of methods used for functional encryption in the academic and professional communities. The book covers functional encryption algorithms and its modern applications in developing secure systems via entity authentication, message authentication, software security, cyber security, hardware security, Internet of Thing (IoT), cloud security, smart card technology, CAPTCHA, digital signature and digital watermarking. Explains the latest functional encryption algorithms in a simple way with examples; Includes applications of functional encryption in information security, application security, and network security; Relevant to academics, research scholars, software developers, etc.